Construção de Conceitos Matemáticos na Educação Básica numa Abordagem Peirceana - Santiago Manechine, Selma Rosana [UNESP]; de Andrade Caldeira, Ana Maria [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2010)
Peircean semiotic analysis is employed to examine the construction/representation of signs-thinking of 32 early elementary school students regarding the concept of length measurement. The work consisted of developing concepts of standard unit, reading and interpretation of measurement by instruments, so that the mathematical language presented in the concrete materials was being signified and re-signified as a tool for perception and representation of new concepts. The pedagogical triad Feeling-Perceiving, Relating-Concept (F-P/R/C) co-related with the dynamism of the semiosis process, defined by Charles Sanders Peirce (1839-1914) in his semiotic theory on the production of the sign (Object, Representamen and Interpretant), enabled the interpretation and analysis of the students' inferences in the phase of perception (feel, admire), induction (experience), and deduction (concept).
A Peircean Approach to the Construction of Mathematical Concepts in Elementary Education
Keywords: Peircean Semiotic; Mathematical Language; Basic Education